L-Band Electron Paramagnetic Resonance Tooth Dosimetry Applied to Affected Cattle Teeth in Fukushima - Ichiro Yamaguchi; Kazuhiko Inoue; Masahiro Natsuhori; Chryzel Angelica B. Gonzales; Hiroshi Yasuda; Yasuhiro Nakai; Minoru Miyake; Harold M. Swartz (Applied Sciences, 2021)
We applied a non-destructive tooth dosimetry technique using L-band electron paramagnetic resonance (EPR) to assess radiation doses in cattle due to the Fukushima Daiichi Nuclear Power Station (FDNPS) accident, which occurred 10 years ago. The radiation exposure of cattle in the area affected by the FDNPS accident was estimated retrospectively with X-band and L-band EPR devices. Characteristic radiation-induced EPR signals were obtained from the teeth of the cattle in Fukushima, confirming their exposure. The estimated doses to the teeth were found to be consistent with the dose trends estimated for individual cows, while considerable uncertainties were seen in the doses of some tooth samples. This variation might be due to errors in the accuracy of the method but also might reflect the actual exposure because the cattle may have been exposed to higher areas of radioactivity in their quest for food and/or due to irradiation from absorption of the isotopes with localization in or near the teeth. However, at a minimum, these results confirm that L-band EPR can be used for non-destructive qualitative assessment of radiation exposure to animals using their teeth, which could be very valuable. Possible causes of the uncertainties should be investigated to enhance the value of the use of this technique.